2016
DOI: 10.1080/13588265.2016.1243609
|View full text |Cite
|
Sign up to set email alerts
|

The effect of placenta location on the safety of pregnant driver and her fetus

Abstract: Citation: ACAR, B. and MERIC, M., 2016. The effect of placenta location on the safety of pregnant driver and her fetus. International Journal of Crashworthiness, 22 (2), pp.163-168. ABSTRACTPlacental abruption accounts for more than half of fetal mortality in automobile collisions. In most of the pregnancies, placenta is located at the fundus position of the uterus. However, in real life, placenta can also be found at different locations in the uterus.The goal of this study is to investigate whether the locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Another plausible explanation is that an anterior placenta is more exposed to external forces during pregnancy compared to a posterior placenta. Acar et al reported a higher risk of placental abruption among pregnant drivers with an anterior placenta than among those with other placental positions [27]. This suggests that an anterior placenta, which is exposed to relatively continuous external in uences during pregnancy, may experience weaker implantation in the uterine wall, resulting in placenta-mediated disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible explanation is that an anterior placenta is more exposed to external forces during pregnancy compared to a posterior placenta. Acar et al reported a higher risk of placental abruption among pregnant drivers with an anterior placenta than among those with other placental positions [27]. This suggests that an anterior placenta, which is exposed to relatively continuous external in uences during pregnancy, may experience weaker implantation in the uterine wall, resulting in placenta-mediated disorders.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Furthermore, airbags seem to be contributing to the protection of both pregnant drivers and their fetuses. 44 …”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, airbags seem to be contributing to the protection of both pregnant drivers and their fetuses. 44 The results of this systematic review provide evidence informing primary prevention measures, recommendations and educational interventions for pregnant women in the context of MVC that should be incorporated into the primary care guidelines.…”
Section: Meaning Of the Studymentioning
confidence: 99%